Eloí, Eloí, Lemá Sabactani? No reflexo de Jesus a imagem de Deus e do humano: uma análise teológica e psicanalítica da onipotência e do desamparo - Armange, Marcos Augusto (2012)
The academic work examines the ideas of Sigmund Freud's psychoanalysis of the human being and the religious, as hermeneutical keys using the concepts of omnipotence and helplessness. For the process of becoming human, it is necessary that, in the course of life, the subject leaves surrounding the omnipotence of his early childhood and assumes progressively helplessness as the vision of becoming itself. Within this context, Freud believes that the religious phenomenon has a negative utility role. In the arduous task of abandonment of narcissism, religion, in the service of the illusions and the neurosis, is created by culture, to support the omnipotence that the person / civilization can not let go, from one God the father all powerful, which is the child's own longing desire. The author highlights the relational ability aspect of God expressed in Jesus Christ event as theological response to the criticisms Freudian. Jesus is seen simultaneously as the God who empties himself of power, which takes the path of the cross, in the deepest distress, and as the man who portrays the authentic humanity, in a sustained helplessness.